Scheme for Processing Mainline Gas at Gas Distribution Stations Using Regenerative Heat Exchangers - Baranov A.Yu.; Kravchenko Yu.A.; Kravchenko D.V.; Baranov M.V. (Problems of the Regional Energetics, 2025)
The article presents the results of a study on optimization of the natural gas purification and dry-ing process in the production of liquefied natural gas (LNG) at gas distribution stations (GDS). The aim of the work is to reduce energy costs at a small-scale natural gas liquefaction plant. To achieve this goal, the following tasks were solved: analysis of existing process flow charts for obtaining LNG at GDS and formulation of their advantages and disadvantages, description of a mathematical model of a recuperative heat exchanger. As part of the study, an analysis of small-scale LNG production technologies was carried out, which showed that the most attractive in terms of energy costs is obtaining liquefied gas in a throttle cycle, and their disadvantages asso-ciated with the organization of the processes of drying and cleaning natural gas before liquefac-tion are shown. The most important result of the study is the development of a process flow chart for processing main gas at GDS using recuperative heat exchangers. The significance of the results lies in reducing energy costs for the processes of gas preparation for liquefaction in the liquefied gas production unit at gas distribution stations. The paper describes a mathematical model of a recuperative heat exchanger developed for setting up a computational experiment to assess the efficiency of recuperative heat exchangers in a natural gas liquefaction cycle, as well as for modeling the processes occurring in recuperative heat exchangers of liquefied natural gas production plants.